Corrigendum to “Fortification of coffee with iron compounds to enhance its micronutrient profile” [Food Chem. 489 (2025) 144964] - B.S. Yashwanth; Vijay Laxmi Biswal; R. Suhas; Sachin R. Chaudhari; J. Naveen; Pushpa S. Murthy (Food Chemistry, 2026)

Pediococcus acidilactici JUFB as a probiotic antibiofilm adjunct against Enterococcus faecalis in persistent endodontic infections - Arpitha Somayaji; R. Manjushree; Sushma S. Murthy; Mohammed Aman (Antonie van Leeuwenhoek, 2026)

Machine‑Learning‑Assisted Experimental Investigation and Multi‑objective Optimization of Cutting Drum Design and Operating Parameters for Surface Miners Using a Rotary Cutting Rig - Hemant Kumar; L. A. Kumaraswamidhas; V. M. S. R. Murthy (Rock Mechanics and Rock Engineering, 2026)

Statistical simulation of extreme storm events and wave climates off the Puducherry coast, western Bay of Bengal - R. Mahesh; G.M. Mridula; S.K. Raju; S. Preethi; V. Ramanathan; M.V. Ramana Murthy; R.S. Kankara (Ocean Engineering, 2026)

A stochastic multivariate extreme-value model for storm and wave climate off the west coast of India - R. Mahesh; S. Preethi; S.K. Raju; J. Satheesh Kumar; V. Ramanathan; M.V. Ramana Murthy; R.S. Kankara (Ocean Engineering, 2026)

Evaluating coastal vulnerability: mapping inundation risk in Tamil Nadu with and without coastal protection - T. Mayamanikandan; Tune Usha; S. K. Dash; S. K. Raju; R. S. Mahendra; M. V. Ramana Murthy (Journal of Coastal Conservation, 2025)

Seasonal dynamics of wave- and tide-dominated beaches: A comprehensive study of beach morphology and sediment characteristics along the east coast of India - Ateeth Shetty; Satya Kiran Raju Alluri; R S Kankara; S Subburaj; V Ramanathan; M V Ramana Murthy (Journal of Earth System Science, 2025)

Fortification of coffee with iron compounds to enhance its micronutrient profile - B.S. Yashwanth; Vijay Laxmi Biswal; R. Suhas; Sachin R. Chaudhari; J. Naveen; Pushpa S. Murthy (Food Chemistry, 2025)

Geo-spatial Impact Evaluation of Developmental Initiatives in a Water-Sensitive Region of India Supporting Sustainable Development Goals - Suneetha Manne; Veeramallu Satya Sahithi; Radhesyam Vaddi; Hemanth Cheepulla; Girish S. Pujar; M. S. R. Murthy (International Journal of Environmental Research, 2025)

Seismic interpretation for comprehending rock characteristics in underground coal mines – some investigations - Avinash Paul; V M S R Murthy; Amar Prakash; Ajoy Kumar Singh (Journal of Earth System Science, 2025)

Zooplankton community changes across the Coringa mangrove and adjacent waters of east coast of India: insights into habitat-specific interactions with environmental changes - P. Ezhilarasan; U. S. Panda; Pandiya rajan R. S; Akhilesh Vijay; M. Kumaraswami; T. P. S. Jinoj; M. V. Ramana Murthy (Environmental Monitoring and Assessment, 2025)

Skin can Modulate the pH of Topical Creams and Gels - Sanjeevini M; Harini Priya Pa; Rakshitha L; Prajwal N. Murthy; Pragathi S. G; Anusha V. Matadh; Srujana N. Murthy; Srinath R; Shivakumar H. N; Howard Maibach; S. Narasimha Murthy (AAPS PharmSciTech, 2025)

Enhanced rainfall forecasting for Mumbai using data-driven ConvLSTM2D models at fine spatial and temporal scales - Akshay Sunil; Ajay Devda; R. Murthy; B. Deepthi (Natural Hazards, 2025)

Exploring the utilization potential of Lantana camara: particleboard and briquette development - V. R. Ramkumar; K. Thanigai; Ritesh Kumar; G. Murali; V. Prakash; Veer Singh Gautam; Manish Ranjan; Narasimha Murthy (Journal of the Indian Academy of Wood Science, 2025)

Influence of Fossil Fuels on Carbonaceous Aerosols: A Comparison among Urban Locations in India - Atar Singh Pipal; R. Latha; B. S. Murthy; A. S. Panicker (Aerosol Science and Engineering, 2025)

New host copepod for the epizoic diatom Protoraphis atlantica from the coastal waters of the Bay of Bengal - A. Anjusha; R. S. Sathishkumar; V. Manigandan; K. Ramu; M. V. Ramana Murthy (Symbiosis, 2025)

Photoluminescence and Decay Kinetic Studies of Eu3+ Activated Novel Magnesium Tungstate Double Perovskite for Lighting Application - Jitesh Sharma; Naresh Degda; Yashesh Gandhi; K. V. R. Murthy (Journal of Fluorescence, 2025)

Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

Associations of exposure to PM2.5 and its compounds with carotid intima-media thickness among middle-aged adults - Kyeezu Kim; Jie Yao; David R. Jacobs; Randall V. Martin; Aaron van Donkelaar; Wei-Chung Su; Chunchao Zhang; Xiang Chen; Venkatesh L. Murthy; Xuehong Zhang; Donald Lloyd-Jones; Lifang Hou; et al. (Science of The Total Environment, 2024)

Temporal variability of ozone and its precursors at tropical megacity, Bengaluru, India: Effect of volatile organic compounds and meteorology - G. Dhanya; T.S. Pranesha; Sandip Nivdange; Kamsali Nagaraja; B.S. Murthy; D.M. Chate; Gufran Beig; Nitin R. Karmalkar (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Synoptic changes and contribution of carbonaceous aerosols to spectral absorption coefficient along with radiative forcing in Himalayan region - Atar S. Pipal; A.S. Panicker; Parminder Kaur; A.S. Gautam; R. Latha; S. Kumar; B.S. Murthy (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Comparative Study of Impact of Gamma and MeV Ion Irradiations on Electrical and Optical Properties Polystyrene/Eu2O3 Nanocomposites - Shilpa Bhavsar; N. L. Singh; K. V. R. Murthy (Journal of Fluorescence, 2024)

Exploration of interaction interface of TRKβ/BDNF through fingerprint analysis to disinter potential agonists - G. N. S. Hemasree; Kshreeraja S. Satish; Saraswathy Ganesan Rajalekshmi; Raghunadha R. Burri; T. P. Krishna Murthy (Molecular Diversity, 2024)

Atmospheric gaseous mercury and associated health risk assessment in the economic capital of India - M. Nageswar Rao; R. Latha; K. Nikhil; B. S. Murthy (Environmental Monitoring and Assessment, 2024)

Responses of plankton community to threshold metal concentrations of cadmium and lead in a mesocosm experiment at Bay of Bengal - Pitchaikkaran Raja; Shambanagouda R. Marigoudar; Panneerselvam Karthikeyan; Sarvalingam Barath Kumar; Avula Nagarjuna; Tanuku Naga Radha Srinivas; Moturi Srirama Krishna; Krishna Venkatarama Sharma; Mallavarapu Venkata Ramana Murthy (Journal of Environmental Management, 2024)

Determination of biogeochemical rate constants for Chilika Lake, a tropical brackish water lagoon on the east coast of India - Sivaji Patra; Charan Kumar Basuri; Pradipta R. Muduli; Vishnu Vardhan Kanuri; Robin R. S.; Ganguly Dipnarayan; Abhilash K. R.; Lovaraju Avvari; Uma Sankar Panda; Dash S. K.; Ramana Murthy M. V. (Frontiers in Marine Science, 2024)

Characterization and prediction of southwest monsoon rainfall patterns in Central India as a linear state space modeling - K. V. Narasimha Murthy; R. Saravana; K. Vijaya Kumar (Natural Hazards, 2024)

Pulped natural/honey robusta coffee fermentation metabolites, physico-chemical and sensory profiles - K.N. Aswathi; Ayusha Shirke; Aishwarya Praveen; Sachin R. Chaudhari; Pushpa S. Murthy (Food Chemistry, 2023)

Multi-year observations of particulate matter and gases over Mumbai: Spatio-temporal variation, oxidation ratios, and secondary aerosols - Nikhil Korhale; Vrinda Anand; R. Latha; B.S. Murthy (Atmospheric Pollution Research, 2023)

Diversity and impacts of macroalgae and cyanobacteria on multi-stressed coral reefs in the Gulf of Mannar Marine Biosphere Reserve - CH. Ramesh; V.R. Prasastha; T. Shunmugaraj; P. Karthick; R. Mohanraju; S. Koushik; M.V.R. Murthy (Marine Environmental Research, 2023)

Spatial distribution of total petroleum hydrocarbons in the seawater and sediment of Southeast coast of India - S. Barath Kumar; M. Savurirajan; P. Raja; S. R. Marigoudar; K. V. Sharma; M. V. Ramana Murthy (Environmental Monitoring and Assessment, 2023)

Biological and physical selectors for mobile biofilms, aerobic granules, and densified-biological flocs in continuously flowing wastewater treatment processes: A state-of-the-art review - Glen T. Daigger; Jacqueline Kuo; Nicolas Derlon; Dwight Houweling; Jose A. Jimenez; Bruce R. Johnson; James P. McQuarrie; Sudhir Murthy; Pusker Regmi; Clement Roche; Belinda Sturm; Bernhard Wett; et al. (Water Research, 2023)

Black Carbon Characteristics over a Semi-urban Environment in the Garhwal Himalayas - A. S. Panicker; K. Sandeep; A. S. Gautam; S. Kumar; G. Beig; R. Latha; B. S. Murthy (Pure and Applied Geophysics, 2023)

Electrochemical conversion of biomass-derived aldehydes into fine chemicals and hydrogen: A review - Jayaraman Theerthagiri; K. Karuppasamy; Juhyeon Park; Nihila Rahamathulla; M. L. Aruna Kumari; Marciélli K. R. Souza; Eduardo S. F. Cardoso; Arun Prasad Murthy; Gilberto Maia; Hyun-Seok Kim; Myong Yong Choi (Environmental Chemistry Letters, 2023)

An intelligent optimized cyclone intensity prediction framework using satellite images - C. Kishor Kumar Reddy; P. R. Anisha; Marlia Mohd Hanafiah; Y. V. S. S. Pragathi; B. V. Ramana Murthy; R. Madana Mohana (Earth Science Informatics, 2023)

Pollution characteristics and ecological risks of trace elements in PM2.5 over three COALESCE network sites - Bhopal, Mesra, and Mysuru, India - Diksha Haswani; Ramya Sunder Raman; Kajal Yadav; Abisheg Dhandapani; Jawed Iqbal; R. Naresh Kumar; S.V. Laxmi Prasad; Adi Yogesh; Sadashiva Murthy B.M.; K.S. Lokesh (Chemosphere, 2023)

Seasonal distribution of microplastics in surface waters of the Northern Indian Ocean - R. Janakiram; R. Keerthivasan; R. Janani; S. Ramasundaram; M.V. Martin; R. Venkatesan; M.V. Ramana Murthy; Tata Sudhakar (Marine Pollution Bulletin, 2023)

Assessment of mangrove stand biomass in relation to forest structural attributes in Bhitarkanika National Park, India - Muktipada Panda; Nikhil Lele; T. V. R. Murthy; R. N. Samal; A. K. Pattnaik; Sudam C. Sahu (Vegetos, 2023)

Compendious Index for Drillability: a rapid tool to assess drill penetration rate and bit life for rock engineering applications - B. N. V. Siva Prasad; V. M. S. R. Murthy; Sripad R. Naik (Bulletin of Engineering Geology and the Environment, 2023)

Decoding rate of penetration of tunnel boring machine in Deccan Traps under varied geological and machine variables using response surface analysis - Anshul Sindhwani; V. M. S. R. Murthy; Md. Raphique; A. K. Raina (Bulletin of Engineering Geology and the Environment, 2023)

On the transition of major pollutant and O3 production regime during Covid-19 lockdowns - Latha R; Shahana Bano; Dolly More; Rupal Ambulkar; Trina Mondal; Priyadarshi Maurya; Murthy BS (Journal of Environmental Management, 2023)

Coupled physical-biogeochemical simulations of upwelling, ecological response to fresh water - Anitha Gera; R Gayathri; P Ezhilarasan; V Ranga Rao; M V Ramana Murthy (Ecological Modelling, 2023)

Seismic energy prediction to optimize rock fragmentation: a modified approach - A. Agrawal; B. S. Choudhary; V. M. S. R. Murthy (International Journal of Environmental Science and Technology, 2022)

Festival Ushered Pollutants in Indian Metropolitan Cities: Resemblance, Variance, and Concerns - Latha R; Vrinda Anand; Nikhil Korhale; Pramod Kori; Murthy B S (Environmental Processes, 2022)

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Prediction of TBM Disc Cutter Wear and Penetration Rate in Tunneling Through Hard and Abrasive Rock Using Multi-layer Shallow Neural Network and Response Surface Methods - Anil Kumar Agrawal; V. M. S. R. Murthy; Somnath Chattopadhyaya; A. K. Raina (Rock Mechanics and Rock Engineering, 2022)

Prolonged effects of DPP-4 inhibitors on steato-hepatitic changes in Sprague–Dawley rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

Three Decades of Indian Remote Sensing in Coastal Research - M. V. Ramana Murthy; Tune Usha; R. S. Kankara (Journal of the Indian Society of Remote Sensing, 2022)

Modelling and forecasting for monthly surface air temperature patterns in India, 1951–2016: Structural time series approach - K V Narasimha Murthy; R Saravana; G Kishore Kumar; K Vijaya Kumar (Journal of Earth System Science, 2021)

Assessment of biogrowth assemblages with depth in a seawater intake system of a coastal power station - T. Subba Rao; P. S. Murthy; P. Veeramani; D. S. Narayanan; R. Ramesh; B. N. Jyothi; D. Muthukumaran; M. Murugesan; A. Vadivelan; G. Dharani; J. Santhanakumar; G. A. Ramadass (Biofouling, 2021)

Seasonal variation in photosynthetic rates and satellite-based GPP estimation over mangrove forest - N. Lele; M. K. Kripa; M. Panda; S. K. Das; A. Hari Nivas; N. Divakaran; S. Naik-Gaonkar; A. Sawant; A. K. Pattnaik; R. N. Samal; T. Thangaradjou; A. Saravanakumar; et al. (Environmental Monitoring and Assessment, 2021)

Correction to: Particulate Matter and Black Carbon in the Brahmaputra Valley of Northeast India: Observations and Model Simulation - B. S. Murthy; R. Latha; R. Srinivas; G. Beig (Pure and Applied Geophysics, 2020)

Particulate Matter and Black Carbon in the Brahmaputra Valley of Northeast India: Observations and Model Simulation - B. S. Murthy; R. Latha; R. Srinivas; G. Beig (Pure and Applied Geophysics, 2020)

Crustal architecture and rift tectonics across the Visakhapatnam Bay basin, central-east Indian margin: Insights from multichannel seismic and potential field data - Pranaya Sangvai; G Srinivasa Rao; K S R Murthy; M Radhakrishna (Journal of Earth System Science, 2020)

Characteristics and Variability of Carbonaceous Aerosols over a Semi Urban Location in Garhwal Himalayas - K. Sandeep; R. S. Negi; A. S. Panicker; Alok Sagar Gautam; D. S. Bhist; G. Beig; B. S. Murthy; R. Latha; Santosh Singh; S. Das (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Seasonal Dynamics and Light Use Efficiency of Major Mangrove Species Over Indian Region - M. K. Kripa; A. Hari Nivas; Nikhil Lele; T. Thangaradjou; A. Saravana Kumar; Archana U. Mankad; T. V. R. Murthy (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Development of pepper vein banding virus chimeric virus-like particles for potential diagnostic and therapeutic applications - Pallavi Sabharwal; C. Sushmitha; C. K. Amritha; Usha Natraj; Mathur R. N. Murthy; Handanahal S. Savithri (Archives of Virology, 2020)

Controlling backbreak and enhancing fragmentation in dragline bench blasting—a geo-engineering approach - Nachiket V. Bhagade; V. M. S. R. Murthy (Arabian Journal of Geosciences, 2020)

Understanding socio-ecological drivers of fuelwood dynamics and their impact in Churia hills of Nepal - Vishwas S. Chitale; M. S. R. Murthy; Hammad Gilani; Rucha Ghate (Tropical Ecology, 2020)

Evolution of the probability distribution function of shovel–dumper combination in open cast limestone mine using RWB and ANN: a case study - N. S. Harish Kumar; R. P. Choudhary; Ch. S. N. Murthy (Modeling Earth Systems and Environment, 2019)

Expression patterns of l-amino acid receptors in the murine STC-1 enteroendocrine cell line - Hongxia Wang; Karnam S. Murthy; John R. Grider (Cell and Tissue Research, 2019)

Aerosol-induced perturbation of surface fluxes over different landscapes in a tropical region - R. Latha; B. S. Murthy; B. Vinayak (International Journal of Remote Sensing, 2019)

Estimates of Carbonaceous Aerosol Radiative Forcing over a Semiurban Environment in Garhwal Himalayas - A. S. Panicker; K. Sandeep; R. S. Negi; A. S. Gautam; D. S. Bisht; G. Beig; B. S. Murthy; R. Latha; Santosh Singh; S. Das (Pure and Applied Geophysics, 2019)

Unobserved component modeling for seasonal rainfall patterns in Rayalaseema region, India 1951–2015 - K. V. Narasimha Murthy; R. Saravana; P. Rajendra (Meteorology and Atmospheric Physics, 2019)

Co-infection of Newcastle disease virus genotype XIII with low pathogenic avian influenza exacerbates clinical outcome of Newcastle disease in vaccinated layer poultry flocks - V. Gowthaman; S. D. Singh; K. Dhama; M. A. Ramakrishnan; Y. P. S. Malik; T. R. Gopala Krishna Murthy; R. Chitra; M Munir (VirusDisease, 2019)

Water Column Effects on In Situ Spectral Signatures of Coral Species from Gujarat Coast, India - Nandini Ray Chaudhury; Ashwin Gujrati; T. V. R. Murthy (Journal of the Indian Society of Remote Sensing, 2019)

Stochastic modelling of the monthly average maximum and minimum temperature patterns in India 1981–2015 - K. V. Narasimha Murthy; R. Saravana; K. Vijaya Kumar (Meteorology and Atmospheric Physics, 2019)

Experimental and Numerical Simulation of Crack Propagation in Sandstone by Semi Circular Bend Test - Sarbartha Sarkar; Rakesh Kumar; V. M. S. R. Murthy (Geotechnical and Geological Engineering, 2019)

Proton Beam Induced Modification of Luminescence Properties of Polystyrene/Al2O3 Polymer Nanocomposites - Shilpa Bhavsar; N. L. Singh; S. V. Suryanarayana; K. V. R. Murthy (Journal of Fluorescence, 2019)

The incretin enhancer, sitagliptin, exacerbates expression of hepatic inflammatory markers in rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Laura A. Forney; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2019)

Development of sesbania mosaic virus nanoparticles for imaging - G. P. Vishnu Vardhan; M. Hema; C. Sushmitha; H. S. Savithri; Usha Natraj; M. R. N. Murthy (Archives of Virology, 2019)

Modelling forest resilience in Hindu Kush Himalaya using geoinformation - M D Behera; M S R Murthy; P Das; E Sharma (Journal of Earth System Science, 2018)

A Spectro-radiometric Analysis of Ocean Colour Sensors and Proposal for a Miniature Hyper Spectral Imager for Future - R. M. Samudraiah Desu; Ashutosh Kumar Jha; Senthil Kumar Arumugam; V. N. Krishna Murthy Yelisetty; Ujjwal Kumar; Kusum Arunachalam (Journal of the Indian Society of Remote Sensing, 2018)

WRF simulation of a severe hailstorm over Baramati: a study into the space–time evolution - B. S. Murthy; R. Latha; H. Madhuparna (Meteorology and Atmospheric Physics, 2018)

Modeling and forecasting rainfall patterns of southwest monsoons in North–East India as a SARIMA process - K. V. Narasimha Murthy; R. Saravana; K. Vijaya Kumar (Meteorology and Atmospheric Physics, 2018)

Quantifying nationwide land cover and historical changes in forests of Nepal (1930–2014): implications on forest fragmentation - C. Sudhakar Reddy; S. Vazeed Pasha; K. V. Satish; K. R. L. Saranya; C. S. Jha; Y. V. N. Krishna Murthy (Biodiversity and Conservation, 2018)

Modeling of high step-up converter in closed loop for renewable energy applications - R. Nagaraj; D. Thiruganamurthy; Manik Murthy Rajput (Environment, Development and Sustainability, 2017)

A composite index for drought hazard assessment using CPC rainfall time series data - C. S. Murthy; J. Singh; P. Kumar; M. V. R. Sesha Sai (International Journal of Environmental Science and Technology, 2017)

Climate and topographic controls on snow cover dynamics in the Hindu Kush Himalaya - Deo Raj Gurung; Sudan Bikash Maharjan; Anu Bhalu Shrestha; Mandira Singh Shrestha; Sagar Ratna Bajracharya; M. S. R. Murthy (International Journal of Climatology, 2017)
Snow governs interaction between atmospheric and land surface processes in high mountains, and is also source of fresh water. It is thus important to both climate scientists and local communities. However, our understanding of snow cover dynamics in terms of space and time is limited across the Hindu Kush Himalaya ( HKH ) region, which is known to be a climatically sensitive region. We used MODIS snow cover area ( SCA ) data (2003–2012), APHRODITE temperature data (2000–2007), and monthly long term in‐situ river discharge data of the Gandaki (1968–2010), Koshi (1977–2010) and Manas (1987–2004) basins to analyse variations among four basins. We gained insights into short term SCA and temperature, long term discharge trends, and regional variability thereby. Strong correlations were observed among SCA , temperature and discharge thereby highlighting the strong nexus between them. Temporal and spatial snow cover variability across the basins is strongly coupled with the variability of two weather systems: Western Disturbances ( WD ) and Indian Monsoon System ( IMS ), and strongly influenced by topography. Manifestation of these variability in terms if downstream discharge can have repercussion to water based sectors: hydropower and agriculture, as low flow seasons is seen affected. This study adds to our knowledge of snow fall and melt dynamics in the HKH region, and intra‐annual snow melt contributions to downstream discharges. The study is limited by short span of data and it is desirable to perform a similar study using data representing a much longer time span.

Movement and home range characteristics of reintroduced tiger (Panthera tigris) population in Panna Tiger Reserve, central India - M. S. Sarkar; K. Ramesh; J. A. Johnson; S. Sen; P. Nigam; S. K. Gupta; R. S. Murthy; G. K. Saha (European Journal of Wildlife Research, 2016)

Biodistribution and toxicity evaluation of sesbania mosaic virus nanoparticles in mice - G. P. Vishnu Vardhan; H. S. Savithri; M. R. N. Murthy; M. Hema (Archives of Virology, 2016)

Identification of Potential Habitat Patches for Connectivity Using Weighted Linear Combination (WLC) and Integral Index of Connectivity (IIC) at East Godavari District, Andhra Pradesh, India - Shanthala Devi B. S; M. S. R Murthy; Debnath Bijan; C. S. Jha (Journal of the Indian Society of Remote Sensing, 2016)

Geospatial Approach for National Level TOF Assessment Using IRS High Resolution Imaging: Early Results - G. S. Pujar; V. K. Dadhwal; M. S. R. Murthy; S. Trivedi; P. M. Reddy; D. Swapna; C. S. Jha (Journal of the Indian Society of Remote Sensing, 2016)

Preparation and Photoluminescence of Sm 3+ Doped YAlO 3 Phosphor - Huma Nazli Baig; Jagjeet Kaur Saluja; D. Harnath; A. S. Sai Prasad; K. V. R. Murthy (Journal of Fluorescence, 2016)

Meteorological drought analysis over India using analytical framework on CPC rainfall time series - C. S. Murthy; Jyoti Singh; Pavan Kumar; M. V. R. Sesha Sai (Natural Hazards, 2016)

Crustal structure and rift tectonics across the Cauvery–Palar basin, Eastern Continental Margin of India based on seismic and potential field modelling - D TWINKLE; G SRINIVASA RAO; M RADHAKRISHNA; K S R MURTHY (Journal of Earth System Science, 2016)

Prediction of Flyrock Distance in Open Pit Blasting Using Surface Response Analysis - A. K. Raina; V. M. S. R. Murthy (Geotechnical and Geological Engineering, 2016)

Synthesis and Photoluminescence Studies of Eu(III), Er(III) Doped Strontium Gadolinium Tantalum Oxide - Verma Vishwnath; Mangalampalli Srinivas; Nimesh P. Patel; Dhaval Modi; K. V. R. Murthy (Journal of Fluorescence, 2016)

Adsorption studies of toxic metals and dyes on soil colloids and their transport in natural porous media - R. Murali; C. N. Murthy; R. A. Sengupta (International Journal of Environmental Science and Technology, 2015)

The SARAL/AltiKa Altimetry Satellite Mission - Jacques Verron; Pierre Sengenes; Juliette Lambin; Jocelyne Noubel; Nathalie Steunou; Amandine Guillot; Nicolas Picot; Sophie Coutin-Faye; Rashmi Sharma; R. M. Gairola; D. V. A. Raghava Murthy; James G. Richman; et al. (Marine Geodesy, 2015)

A seismotectonic study of the 21 May 2014 Bay of Bengal intraplate earthquake: evidence of onshore-offshore tectonic linkage and fracture zone reactivation in the northern Bay of Bengal - G. Srinivasa Rao; M. Radhakrishna; K. S. R. Murthy (Natural Hazards, 2015)

Nearshore Wave Climate and Sediment Dynamics along South East Coast of India - Usha Natesan; P. R. Rajalakshmi; M. V. Ramana Murthy; Vincent A Ferrer (Journal of the Indian Society of Remote Sensing, 2015)

Synthesis and Evaluation of Substituted Poly(organophosphazenes) as a Novel Nanocarrier System for Combined Antimalarial Therapy of Primaquine and Dihydroartemisinin - Sahil Kumar; Rajesh K. Singh; R. S. R. Murthy; T. R. Bhardwaj (Pharmaceutical Research, 2015)

A study on agricultural drought vulnerability at disaggregated level in a highly irrigated and intensely cropped state of India - C. S. Murthy; Manoj Yadav; J. Mohammed Ahamed; B. Laxman; R. Prawasi; M. V. R. Sesha Sai; R. S. Hooda (Environmental Monitoring and Assessment, 2015)

Synthesis and mosquito larvicidal activity of furanochalcones and furanoflavonoids analogous to karanjin - Susarla R. Satyavani; Sanjit Kanjilal; Muthineni S. Rao; Rachapudi B. N. Prasad; Upadyayula S. N. Murthy (Medicinal Chemistry Research, 2015)

Regulation of Gβγi-Dependent PLC-β3 Activity in Smooth Muscle: Inhibitory Phosphorylation of PLC-β3 by PKA and PKG and Stimulatory Phosphorylation of Gαi-GTPase-Activating Protein RGS2 by PKG - Ancy D. Nalli; Divya P. Kumar; Othman Al-Shboul; Sunila Mahavadi; John F. Kuemmerle; John R. Grider; Karnam S. Murthy (Cell Biochemistry and Biophysics, 2014)

Flyrock in bench blasting: a comprehensive review - A. K. Raina; V. M. S. R. Murthy; A. K. Soni (Bulletin of Engineering Geology and the Environment, 2014)

Predictive models for pot-hole depth in underground coal mining—some Indian experiences - R. D. Lokhande; V. M. S. R. Murthy; K. B. Singh (Arabian Journal of Geosciences, 2014)

Formulation and Evaluation of Sustained Release Extrudes Prepared via Novel Hot Melt Extrusion Technique - Ravindra Tiwari; Sunil Kumar Agarwal; R. S. R. Murthy; Shweta Tiwari (Journal of Pharmaceutical Innovation, 2014)

Deforestation trends and spatial modelling of its drivers in the dry temperate forests of northern Pakistan — A case study of Chitral - Khuram Shehzad; Faisal M. Qamer; M. S. R. Murthy; Sawaid Abbas; Laxmi D. Bhatta (Journal of Mountain Science, 2014)

Extracellular histones in tissue injury and inflammation - Ramanjaneyulu Allam; Santhosh V. R. Kumar; Murthy N. Darisipudi; Hans-Joachim Anders (Journal of Molecular Medicine, 2014)

Coregulation of host–response genes in integument: switchover of gene expression correlation pattern and impaired immune responses induced by dipteran parasite infection in the silkworm, Bombyx mori - Anitha Jayaram; Appukuttan Nair R. Pradeep; Arvind K. Awasthi; Geetha N. Murthy; Kangayam M. Ponnuvel; Sirigineedi Sasibhushan; Guruprasad C. Rao (Journal of Applied Genetics, 2014)

Evaluation of object-based image analysis techniques on very high-resolution satellite image for biomass estimation in a watershed of hilly forest of Nepal - Yousif Ali Hussin; Hammad Gilani; Louise van Leeuwen; M. S. R. Murthy; Rachna Shah; Srijana Baral; Nandin-Erdene Tsendbazar; Saurav Shrestha; Shyam Kumar Shah; Faisal Mueen Qamer (Applied Geomatics, 2014)

Potential use of Caulerpa fastigiata biomass for removal of lead: kinetics, isotherms, thermodynamic, and characterization studies - B. Sarada; M. Krishna Prasad; K. Kishore Kumar; Ch. V. R. Murthy (Environmental Science and Pollution Research, 2014)

Estimation of wave heights during cyclonic conditions using wave propagation model - Usha Natesan; P. R. Rajalakshmi; M. V. Ramana Murthy; Vincent A. Ferrer (Natural Hazards, 2013)

Assessment of coastal dune characteristics using georadar imaging and sedimentological analysis: Odisha and Visakhapatnam, India - K. Devi; M. C. Raicy; Deshraj Trivedi; P. Srinivasan; S. G. N. Murthy; Ronald J. Goble; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Erratum to: Early-season agricultural drought: detection, assessment and monitoring using Shortwave Angle and Slope Index (SASI) data - Prabir Kumar Das; Srirama C. Murthy; M. V. R. Seshasai (Environmental Monitoring and Assessment, 2013)

Early-season agricultural drought: detection, assessment and monitoring using Shortwave Angle and Slope Index (SASI) data - Prabir Kumar Das; Srirama C. Murthy; M. V. R. Seshasai (Environmental Monitoring and Assessment, 2013)

Evaluation of efficiency of hemi-nested PCR assay for the detection of ‘Candidatus Liberibacter’ infecting citrus - Adpangaya Sahana Bhaskara; Bandalli N. Jawad Ahmed; Charith R. Adkar-Purushothama; Mysore N. Nagendra Prasad; Marikunte Y. Sreenivasa; Pavagada K. Murthy Maheshwar (Journal of Plant Diseases and Protection, 2013)

Environmental impact and cost assessment of incineration and ethanol production as municipal solid waste management strategies - Mir Abbas Bozorgirad; Hao Zhang; Karl R. Haapala; Ganti S. Murthy (The International Journal of Life Cycle Assessment, 2013)

Multi-Criteria Decision Making Approach for Watershed Prioritization Using Analytic Hierarchy Process Technique and GIS - V. M. Chowdary; D. Chakraborthy; A. Jeyaram; Y. V. N. Krishna Murthy; J. R. Sharma; V. K. Dadhwal (Water Resources Management, 2013)

Response of Cassava canopy to mid-day pseudo sunrise induced by solar eclipse - R. Latha; B. S. Murthy (International Journal of Biometeorology, 2013)

Heavy-Metal Fractionation in Surface Sediments of the Cauvery River Estuarine Region, Southeastern Coast of India - S. Dhanakumar; K. Rutharvel Murthy; G. Solaraj; R. Mohanraj (Archives of Environmental Contamination and Toxicology, 2013)

Activation of autophagic programmed cell death and innate immune gene expression reveals immuno-competence of integumental epithelium in Bombyx mori infected by a dipteran parasitoid - Appukuttan Nair R. Pradeep; Jayaram Anitha; Arvind K. Awasthi; Mohd. A. Babu; Murthy N. Geetha; Hariharan K. Arun; Sagar Chandrashekhar; Guruprasad C. Rao; Nanjappa B. Vijayaprakash (Cell and Tissue Research, 2013)

Pot-hole Subsidence in Underground Coal Mining: Some Indian Experiences - R. D. Lokhande; V. M. S. R. Murthy; K. B. Singh (Geotechnical and Geological Engineering, 2013)

Integrated approach of assessing sedimentary characteristics of onshore sand deposits on the Velankanni coast, Tamil Nadu, India: sheds light on extreme wave event signatures - K. Devi; C. S. Vijaya Lakshmi; M. C. Raicy; P. Srinivasan; S. G. N. Murthy; S. M. Hussain; Ilya Buynevich; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Wetland Monitoring, Serving as an Index of Land Use Change-A Study in Samaspur Wetlands, Uttar Pradesh, India - M. D. Behera; V. S. Chitale; A. Shaw; P. S. Roy; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2012)

Synthesis and insect antifeedant activity of plumbagin derivatives - K. Rajendra Prasad; K. Suresh Babu; R. Ranga Rao; G. Suresh; K. Rekha; J. Madhusudana Murthy; P. Usha Rani; J. Madhusudana Rao (Medicinal Chemistry Research, 2012)

Effect of nucleotide on growth, immune responses and resistance of Macrobrachium rosenbergii (De Man) to Macrobrachium rosenbergii nodavirus (MrNV) and extra small virus (XSV) and Aeromonas hydrophila infection - R. Shankar; H. Shivananda Murthy; H. R. Sujatha; E. G. Jayaraj; C. S. Tejpal; V. S. Chinthamani (Aquaculture International, 2012)

Natural reduction of CO2 observed in the pre-monsoon period at the coastal station, Goa - R. Latha; B. S. Murthy (Meteorology and Atmospheric Physics, 2012)

New advanced glycation end-products inhibitors from Dichrostachys cinerea Wight & Arn. - G. Suresh; Ashok K. Tiwari; M. Radha Krishna Murthy; D. Anand Kumar; K. Rajendra Prasad; R. Ranga Rao; A. Zehra Ali; K. Suresh Babu (Journal of Natural Medicines, 2012)

Studies on urban drinking water quality in a tropical zone - Mohana Krishna Reddy Mudiam; S. P. Pathak; K. Gopal; R. C. Murthy (Environmental Monitoring and Assessment, 2012)

Association of Estrogen Receptor-α Gene & Metallothionein-1 Gene Polymorphisms in Type 2 Diabetic Women of Andhra Pradesh - Shilpa Reddy Ganasyam; Talluri Bhaskar Rao; Y. S. R. Murthy; Akka Jyothy; Madireddy Sujatha (Indian Journal of Clinical Biochemistry, 2012)

Antifilarial efficacy of Hibiscus sabdariffa on lymphatic filarial parasite Brugia malayi - K. Saxena; V. Dube; V. Kushwaha; V. Gupta; M. Lakshmi; S. Mishra; S. Gupta; A. Arora; V. Lakshmi; R. K. Sharma; G. K. Jain; P. K. Murthy (Medicinal Chemistry Research, 2011)

Subsurface signatures and timing of extreme wave events along the southeast Indian coast - RAJESH R NAIR; MADHAV K MURARI; C S VIJAYA LAKSHMI; ILYA BUYNEVICH; RON J GOBLE; P SRINIVASAN; S G N MURTHY; DESHRAJ TRIVEDI; SURESH CHANDRA KANDPAL; S M HUSSAIN; D SENGUPTA; ASHOK K SINGHVI (Journal of Earth System Science, 2011)

Guest editorial for the special issue “Tectonics of Bay of Bengal and Arabian Sea with special emphasis on coastal and marine geohazards” - K. S. R. Murthy; A. K. Chaubey; M. Radhakrishna (Natural Hazards, 2011)

Land–ocean tectonics (LOTs) and the associated seismic hazard over the Eastern Continental Margin of India (ECMI) - K. S. R. Murthy; V. Subrahmanyam; A. S. Subrahmanyam; G. P. S. Murty; K. V. L. N. S. Sarma (Natural Hazards, 2010)

Steady- and transient-state effects during the biological oxidation of gas-phase benzene in a continuously operated biofilter - Eldon R. Rene; D. V. S. Murthy; T. Swaminathan (Clean Technologies and Environmental Policy, 2010)

16S rDNA sequence analysis of culturable marine biofilm forming bacteria from a ship's hull - D. Inbakandan; P. Sriyutha Murthy; R. Venkatesan; S. Ajmal Khan (Biofouling, 2010)

A homozygous mutation in LTBP2 causes isolated microspherophakia - Arun Kumar; Maheswara R. Duvvari; Venkatesh C. Prabhakaran; Jyoti S. Shetty; Gowri J. Murthy; Susan H. Blanton (Human Genetics, 2010)

Effect of Flow Rate, Concentration and Transient—State Operations on the Performance of a Biofilter Treating Xylene Vapors - Eldon R. Rene; D. V. S. Murthy; T. Swaminathan (Water, Air, & Soil Pollution, 2010)

Geospatial modeling of biological richness in Kuldiha wildlife sanctuary of Orissa, India - C. Pattanaik; C. S. Reddy; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2010)

Geospatial modelling for identification of potential ecological corridors in Orissa - A. Roy; B. S. S. Devi; B. Debnath; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2010)

Application of landscape ecology and remote sensing for assessment, monitoring and conservation of biodiversity - J. S. Singh; P. S. Roy; M. S. R. Murthy; C. S. Jha (Journal of the Indian Society of Remote Sensing, 2010)

Applications of Numerical Modelling for Strata Control in Mines - G. S. P. Singh; U. K. Singh; V. M. S. R. Murthy (Geotechnical and Geological Engineering, 2010)

Granularity and textural analysis as a proxy for extreme wave events in southeast coast of India - C. S. Vijaya Lakshmi; P. Srinivasan; S. G. N. Murthy; Deshraj Trivedi; Rajesh R. Nair (Journal of Earth System Science, 2010)

The role of post-transcriptional RNA processing and plasmid vector sequences on transient transgene expression in zebrafish - Sumantra Chatterjee; Lin Min; R. Krishna Murthy Karuturi; Thomas Lufkin (Transgenic Research, 2010)

Evaluating forest fragmentation and its tree community composition in the tropical rain forest of Southern Western Ghats (India) from 1973 to 2004 - A. Giriraj; M. S. R. Murthy; C. Beierkuhnlein (Environmental Monitoring and Assessment, 2010)

Monitoring conservation effectiveness in a global biodiversity hotspot: the contribution of land cover change assessment - Shijo Joseph; George Alan Blackburn; Biswadip Gharai; S. Sudhakar; A. P. Thomas; M. S. R. Murthy (Environmental Monitoring and Assessment, 2009)

Magnetic anomalies of offshore Krishna-Godavari basin, eastern continental margin of India - K. V. Swamy; I. V. Radhakrishna Murthy; K. S. Krishna; K. S. R. Murthy; A. S. Subrahmanyam; M. M. Malleswara Rao (Journal of Earth System Science, 2009)

Spatial and temporal responses of different crop‐growing environments to agricultural drought: a study in Haryana state, India using NOAA AVHRR data - C. S. Murthy; M. V. R. Sesha Sai; K. Chandrasekar; P. S. Roy (International Journal of Remote Sensing, 2009)

Multi‐criteria decision evaluation in groundwater zones identification in Moyale‐Teltele subbasin, South Ethiopia - K. S. R. Murthy; Abiy Gatachew Mamo (International Journal of Remote Sensing, 2009)

Wind waves and sediment transport regime off the south-central Kerala coast, India - N. P. Kurian; K. Rajith; T. S. Shahul Hameed; L. Sheela Nair; M. V. Ramana Murthy; S. Arjun; V. R. Shamji (Natural Hazards, 2009)

The Effect of Double Dispersion on Natural Convection Heat and Mass Transfer in a Non-Newtonian Fluid Saturated Non-Darcy Porous Medium - R. R. Kairi; P. A. L. Narayana; P. V. S. N. Murthy (Transport in Porous Media, 2009)

On the influence of spatial heterogeneity on an internal boundary layer at a short fetch - B. S. Murthy; R. Latha; Cini Sukumaran; A. Shivaji; S. Sivaramakrishnan (Journal of Earth System Science, 2009)

Numerical modeling of the 26th December 2004 India Ocean tsunami at Andaman and Nicobar Islands - K. Ilayaraja; M. Ioualalen; M. Chlieh; R. R. Krishnamurthy; M. V. Ramana Murthy (Journal of Coastal Conservation, 2008)

Identification of Brugia malayi adult worm molecules immunoreactive with sera of infected animals treated with antifilarial and re-infected with homologous infection and their role in the establishment of infection in Mastomys coucha - R. L. Gaur; M. K. Sahoo; S. Dixit; S. K. Joseph; P. K. Murthy (Medicinal Chemistry Research, 2008)

Enhancement of Dissolution Rate of Gliclazide Using Solid Dispersions with Polyethylene Glycol 6000 - S. Biswal; J. Sahoo; P. N. Murthy; R. P. Giradkar; J. G. Avari (AAPS PharmSciTech, 2008)

Molecular Diversity in Indian Tobacco Types as Revealed by Randomly Amplified DNA Polymorphism - K. SivaRaju; M. S. Madhav; R. K. Sharma; T. G. K. Murthy; N. K. Singh; K. C. Bansal; K. R. Koundal; T. Mohapatra (Journal of Plant Biochemistry and Biotechnology, 2008)

Investigations of the effect of the lipid matrix on drug entrapment, in vitro release, and physical stability of olanzapine-loaded solid lipid nanoparticles - K. Vivek; Harivardhan Reddy; Ramachandra S. R. Murthy (AAPS PharmSciTech, 2007)

Structure and function of enzymes involved in the anaerobic degradation of L-threonine to propionate - Dhirendra K. Simanshu; Sagar Chittori; H. S. Savithri; M. R. N. Murthy (Journal of Biosciences, 2007)

Inhalation Exposure of Formulated Fenvalerate (20% EC): Toxicologic Alterations in Kidney of Rats - U. Mani; Kewal Lal; P. K. Singh; R. C. Murthy (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Carbon forestry economic mitigation potential in India, by land classification - N. H. Ravindranath; I. K. Murthy; R. K. Chaturvedi; K. Andrasko; J. A. Sathaye (Mitigation and Adaptation Strategies for Global Change, 2007)

Mapping the geographic distribution of Aglaia bourdillonii Gamble (Meliaceae), an endemic and threatened plant, using ecological niche modeling - M. Irfan-Ullah; Giriraj Amarnath; M. S. R. Murthy; A. Townsend Peterson (Biodiversity and Conservation, 2007)

Tablet formulation studies on nimesulide and meloxicam-cyclodextrin binary systems - Buchi N. Nalluri; K. P. R. Chowdary; K. V. R. Murthy; G. Becket; Peter A. Crooks (AAPS PharmSciTech, 2007)

Active forest fire monitoring in Uttaranchal State, India using multi‐temporal DMSP‐OLS and MODIS data - T. R. Kiran Chand; K. V. S. Badarinath; M. S. R. Murthy; G. Rajshekhar; C. D. Elvidge; B. T. Tuttle (International Journal of Remote Sensing, 2007)

Estimation of number of deaths associated with exposure to excess ambient PM10 air pollution - D. Giri; V. K. Murthy; P. R. Adhikary; S. N. Khanal (International Journal of Environmental Science and Technology, 2007)

Performance of upflow anoxic bioreactor for wastewater treatment - S. K. Behera; E. R. Rene; D. V. S. Murthy (International Journal of Environmental Science and Technology, 2007)

The role of inter-subunit ionic interactions in the assembly of Physalis mottle tymovirus - M. Umashankar; M. R. N. Murthy; S. A. Singh; A. G. Appu Rao; H. S. Savithri (Archives of Virology, 2006)

Ambient air quality of Kathmandu valley as reflected by atmospheric particulate matter concentrations (PM10) - D. Giri; K. V. Murthy; P. R. Adhikary; S. N. Khanal (International Journal of Environmental Science and Technology, 2006)

Design and development of microemulsion drug delivery system of acyclovir for improvement of oral bioavailability - Pradip Kumar Ghosh; Rita J. Majithiya; Manish L. Umrethia; Rayasa S. R. Murthy (AAPS PharmSciTech, 2006)

Thermoreversible-mucoadhesive Gel for nasal delivery of sumatriptan - Rita J. Majithiya; Pradip K. Ghosh; Manish L. Umrethia; Rayasa S. R. Murthy (AAPS PharmSciTech, 2006)

Cerebrospinal fluid free sialic acid and aspartate transaminase levels in meningitis - S. P. Kulkarni; C. R. Mallikarjuna; D. S. Jayaprakash Murthy (Indian Journal of Clinical Biochemistry, 2006)

Estimation of petrol and diesel adulteration with kerosene and assessment of usefulness of selected automobile fuel quality test parameters - Sh. R. Yadav; V. K. Murthy; D. Mishra; B. Baral (International Journal of Environmental Science and Technology, 2005)

Time Series Analysis to Monitor and Assess Water Resources: A Moving Average Approach - Rajesh Reghunath; T. R. Sreedhara Murthy; B. R. Raghavan (Environmental Monitoring and Assessment, 2005)

Analysis of Terra Modis satellite data for Ecological Impact Assessment (EcIA) studies - T. R. Kiran Chand; K. Madhavi Latha; K. V. S. Badarinath; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2005)

Use of specific IgE to fractions of gynandropsis gynandra pollen inin vitro diagnostic test - G. Suman Latha; Vijaya Lakshmi; H. Surekha Rani; K. J. R. Murthy (Indian Journal of Clinical Biochemistry, 2005)

Delineation of concealed lineaments using interpreted resistivity values - Rajesh Reghunath; T. R. Sreedhara. Murthy; H. N. Udaya. Shankar (Bulletin of Engineering Geology and the Environment, 2005)

Etoposide-loaded nanoparticles made from glyceride lipids: Formulation, characterization, in vitro drug release, and stability evaluation - L. Harivardhan Reddy; R. S. R. Murthy (AAPS PharmSciTech, 2005)

Potential of Eisenia foetida for Sustainable and Efficient Vermicomposting of Fly Ash - S. K. Gupta; Anamika Tewari; Richa Srivastava; R. C. Murthy; Saurabh Chandra (Water, Air, & Soil Pollution, 2005)

Check dam positioning by prioritization of micro-watersheds using SYI model and morphometric analysis — Remote sensing and GIS perspective - K. Nooka Ratnam; Y. K. Srivastava; V. Venkateswara Rao; E. Amminedu; K. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2005)

Modeling potential forest fire danger using modis data - K. V. S. Badarinath; K. Madhavilatha; T. R. Kiran Chand; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2004)

Satellite-based assessment of physiographic disposition to health problems in kasargod district, Kerala, India - P. P. Nageshwara Rao; S. Elango; H. R. Rajmohan; V. Krishna Murthy (Journal of the Indian Society of Remote Sensing, 2004)

Integration of thematic maps through GIS for identification of groundwater potential zones - K. S. R. Murthy; E. Amminedu; V. Venkateswara Rao (Journal of the Indian Society of Remote Sensing, 2003)

Controlled release formulation of tramadol hydrochloride using hydrophilic and hydrophobic matrix system - Sandip B. Tiwari; T. Krishna Murthy; M. Raveendra Pai; Pavak R. Mehta; Pasula B. Chowdary (AAPS PharmSciTech, 2003)

Physicochemical characterization and dissolution properties of nimesulide-cyclodextrin binary systems - Buchi N. Nalluri; K. P. R. Chowdary; K. V. R. Murthy; A. R. Hayman; G. Becket (AAPS PharmSciTech, 2003)

Productivity optimisation in weak sedimentary formations for improved coal production and roof stability—an approach - V. M. S. R. Murthy; Santosh Kumar Ray (Geotechnical and Geological Engineering, 2002)

In vivo evaluation of modified gum karaya as a carrier for improving the oral bioavailability of a poorly water-soluble drug, nimodipine - Gedela V. Murali Mohan Babu; Namballa R. Kumar; Kasina H. Sankar; Battu J. Ram; Namburu K. Kumar; Kolapalli V. R. Murthy (AAPS PharmSciTech, 2002)

Evidence for recombination among the tomato leaf curl virus strains/species from Bangalore, India - N. Kirthi; S. P. Maiya; M. R. N. Murthy; H. S. Savithri (Archives of Virology, 2002)

Lead neurotoxicity: Heme oxygenase and nitric oxide synthase activities in developing rat brain - Gottipolu R. Reddy; Ambati Suresh; Karnam S. Murthy; Chellu S. Chetty (Neurotoxicity Research, 2002)

Acute and chronic toxicity studies on partially purified hypoglycemic preparation from water extract of bark ofFicus bengalensis - S. Gupta; R. Shukla; K. M. Prabhu; S. Aggrawal; U. Rusia; P. S. Murthy (Indian Journal of Clinical Biochemistry, 2002)

Anaerobic Fluidized Bed Degradation and the Development of a Kinetic Model for a Particulate Organic Matter Enriched Wastewater Sludge - R. Saravanane; D. V. S. Murthy; K. Krishnaiah (Water, Air, & Soil Pollution, 2001)

Physical and chemical permeation enhancers in transdermal delivery of terbutaline sulphate - S. Narasimha Murthy; Shobha Rani R. Hiremath (AAPS PharmSciTech, 2001)

Medicinal plants for treatment of diabetes mellitus - R. Shukia; S. B. Sharma; D. Puri; K. M. Prabhu; P. S. Murthy (Indian Journal of Clinical Biochemistry, 2000)

Loktak notified Wetland ecosystem and its catchment - N Randhir Singh; N S Singh; J K Garg; T V R Murthy (Journal of the Indian Society of Remote Sensing, 2000)

Structure of the Lower Crust Revealed by One- and Two-dimensional Modeling of Wide-angle Reflections -- West Bengal Basin, India - I. B. P. Rao; P. R. K. Murthy; P. Koteswara Rao; A. S. N. Murty; N. Madhava Rao; K. L. Kaila (Pure and Applied Geophysics, 1999)

Culture and regeneration of mesophyll-derived protoplasts of sorghum [ Sorghum bicolor (L.) Moench] - R. V. Sairam; N. Seetharama; P. S. Devi; A. Verma; U. R. Murthy; I. Potrykus (Plant Cell Reports, 1999)

Mapping of hydrogeomorphological features in varaha river basin using IRS data - K S R Murthy; V Venkateswara Rao (Journal of the Indian Society of Remote Sensing, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Wavelet Analysis of Intermittent Turbulent Transport in the Atmospheric Surface Layer over a Monsoon Trough Region - J. R. Kulkarni; L. K. Sadani; B. S. Murthy (Boundary-Layer Meteorology, 1999)

Antitubercular activity of garlic (allium sativum) extract on combination with conventional antitubercular drugs in tubercular lymphadenitis - R. L. Gupta; Sundeep Jain; V. Talwar; H. C. Gupta; P. S. Murthy (Indian Journal of Clinical Biochemistry, 1999)

Chromosomal localization and genomic organization of the human retinal rod Na-Ca+K exchanger - J. E. Tucker; R. J. Winkfein; S. K. Murthy; J. S. Friedman; M. A. Walter; D. J. Demetrick; P. P. M. Schnetkamp (Human Genetics, 1998)

Studies on a new antitubercular drug, trifluoperazine: Its effect in combination with conventional antitubercular drugs in tubercular lymphadenitis - R. L. Gupta; Sundeep Jain; V. Talwar; H. C. Gupta; P. S. Murthy (Indian Journal of Clinical Biochemistry, 1998)

Source and target enzyme signature in serine protease inhibitor active site sequences - Balaji Prakash; M. R. N. Murthy (Journal of Biosciences, 1997)

Studies on simultaneous inhibition of trypsin and chymotrypsin by horsegram Bowman-Birk inhibitor - Balaji Prakash; M. R. N. Murthy; Y. N. Sreerama; D. Rajagopal Rao; Lalitha R. Gowda (Journal of Biosciences, 1997)

Role of immunotherapy in the treatment of tuberculosis - K. J. R. Murthy; V. Vijaya Lakshmi; S. Singh (Indian Journal of Clinical Biochemistry, 1997)

Trifluoperazine and CEF-allicin from garlic (Allium sativum) as potential new antitubercular drugs active against drug resistantMycobacterium tuberculosis - P. S. Murthy; P. Ratnakar; D. V. Gadre; V. Talwar; H. C. Gupta; R. L. Gupta (Indian Journal of Clinical Biochemistry, 1997)

Temporal studies of land use/land cover in varaha river basin, andhra pradesh, india - K S R Murthy; V Venkateswara Rao (Journal of the Indian Society of Remote Sensing, 1997)

Magnetic expression of some major lineaments and Cretaceous quiet zone in the Bay of Bengal - A. S. Subrahmanyam; K. S. R. Murthy; S. Lakshminarayana; M. M. Malleswara Rao; K. Venkateswarlu; T. C. S. Rao (Geo-Marine Letters, 1997)

Studies on some trace and minor elements in blood - T. R. Mahalingam; S. Vijayalashmi; R. Krishna Prabhu; A. Thiruvengadasami; K. S. R. Murthy; Deepak Sen; C. K. Mathews; K. Radha Shanmugasundaram (Biological Trace Element Research, 1997)

Cattle mortality in the Thane district, India: A study of cause/effect relationships - R. K. S. Dogra; R. C. Murthy; A. K. Srivastava; J. S. Gaur; L. J. Shukla; B. M. L. Varmani (Archives of Environmental Contamination and Toxicology, 1996)

Cattle Mortality in the Thane District, India: A Study of Cause/Effect Relationships - R. K. S. Dogra; R. C. Murthy; A. K. Srivastava; J. S. Gaur; L. J. Shukla; B. M. L. Varmani (Archives of Environmental Contamination and Toxicology, 1996)

Nucleotide sequence of the 3? terminal region of belladonna mottle virus-Iowa (renamed Physalis mottle virus) RNA and an analysis of the relationships of tymoviral coat proteins - A. N. K. Jacob; M. R. N. Murthy; H. S. Savithri (Archives of Virology, 1992)

Structure-function relationships of icosahedral plant viruses - H. S. Savithri; S. Suryanarayana; M. R. N. Murthy (Archives of Virology, 1989)

Behavioral and neurochemical changes in rats simultaneously exposed to manganese and lead - Satya V. Chandra; M. Mohd. Ali; D. K. Saxena; R. C. Murthy (Archives of Toxicology, 1981)